Restoration of Properties of Heat-Resistant Steel After Long-Term Operation in Steam Pipeline Bends of TPP by Heat Treatment - Halyna Krechkovska; Ivan Tsybailo; Ihor Dzioba; Oleksandra Student; Robert Pała (Metals)
To improve the microstructure and mechanical properties of heat-resistant 12Kh1MF steel after long-term operation in the stretched bend zone of the main steam pipeline of a thermal power plant, restorative heat treatment (RHT) was proposed. The RHT mode consisted of two normalization stages (from temperatures of 1100 and 960 °C, respectively) followed by tempering at a temperature of 740 °C. The RHT mode, regulated for steel in the initial state, was applied only after its normalization from a significantly higher temperature (1100 °C). It was shown that the proportion of fine grains in the steel structure increased to 55% over the entire pipe wall thickness after using RHT. At the same time, the proportion of large grains in the restored steel decreased significantly (to 10%), while in exploited steel, their proportion reached almost 50%. The proposed RHT mode increased the hardness, strength, plasticity, and resistance to brittle fracture of the restored steel relative to the corresponding characteristics of the operated steel. The maximum positive effect of the RHT was obtained during impact testing. The fractographic features of the exploited and restored steel were studied on fractures of samples tested by tension. The main fractographic feature of the operated steel was nanosized particles at the bottom of large dimples. These tiny particles were considered to be fragments of large carbides formed due to their final decohesion from the matrix during tensile testing. However, such nanosized particles were not found on the samples’ fracture surfaces in the steel after restorative heat treatment. In addition, the ductile dimples on the fractures of the restored steel were more prominent, which indicated high energy costs for their formation. Thus, all the obtained research results suggest the possibility of using the proposed RHT mode to extend the service life of long-operated critical elements of a thermal power plant’s steam pipelines.